Taking Tiger Worm Toilets to scale: opportunities and challenges - Sioné, Laure; Gibson, Walter; Beckett, Patrick; Oak, Ajeet; Sathre, Roger; Furlong, Claire; Bastable, Andy; Batarda, Carlos; Templeton, Michael R. (Frontiers in Environmental Science, 2023)
Tiger Worm Toilets (TWTs) are a relatively recent innovation in sanitation technology, with the potential to offer affordable and safely managed on-site sanitation for underserved communities in line with Sustainable Development Goal 6. This article, authored by members of the International Worm-Based Sanitation Association (IWBSA 1 ), presents the state-of-the-art in TWT construction and operation based on frontier global experiences to-date, stemming from both knowledge from literature but also from the practical knowledge imparted by the authors, who were involved in the birth of this technology and are still active in the research and deployment of it today. The focus of this paper is on the implementation of TWTs to solve sanitation challenges in least-developed and lower-middle income countries specifically. The design of TWTs can be adapted to a wide range of environmental conditions including high water tables and rocky ground conditions, and in both rural and urban contexts. The challenge for TWTs therefore lies primarily in creating opportunities for scaling the uptake of this promising technology. Our article discusses the key barriers to this, identified to be broadly categorised as user preference, capacity and capability building, and governmental support -and proposes how to overcome these.